Career Adaptability, Work Engagement, and Employee Well-Being Among Chinese Employees: The Role of Guanxi - Yang, Xuhua; Feng, Yaqian; Meng, Yuchen; Qiu, Yong (Frontiers in Psychology, 2019)
The present study examined whether and how career adaptability predicts employee well-being (EWB) based on career construction theory. A three-wave questionnaire design was used to collect the data, and 338 employees participated in the study. The results suggest that career adaptability has a significant effect on work engagement, which, in turn, predicts EWB. In addition to developing a mediation model, we tested the effect of guanxi as a moderator on the former part of the model. Thus, a moderated-mediation model was constructed in this research. In addition to the finding of the mediating role of work engagement, the discussion of guanxi represents a more important novel aspect that draws attention to contextual factors that may shape how employees respond to career adaptability. The results revealed that the indirect effect of career adaptability on EWB through work engagement when guanxi is low is stronger than that when guanxi is high. Furthermore, we discuss the limitations of this study and the implications for future research on career adaptability and EWB.